Minimal Shortening of Leukocyte Telomere Length Across Age Groups in a Cross-Sectional Study for Carriers of a Longevity-Associated FOXO3 Allele. (21st April 2018) - Davy, Philip M C; Willcox, D Craig; Shimabukuro, Michio; Donlon, Timothy A; Torigoe, Trevor; Suzuki, Makoto; Higa, Moritake; Masuzaki, Hiroaki; Sata, Masataka; Chen, Randi; Murkofsky, Rachel L; Morris, Brian J; et al.
Abstract: FOXO3 is one of the most prominent genes demonstrating a consistently reproducible genetic association with human longevity. The mechanisms by which these individual gene variants confer greater organismal lifespan are not well understood. We assessed the effect of longevity-associated FOXO3 alleles on age-related leukocyte telomere dynamics in a cross-sectional study comprised of samples from 121 healthy Okinawan-Japanese donors aged 21–95 years. We found that telomere length for carriers of the longevity associated allele of FOXO3 single nucleotide polymorphism rs2802292 displayed no significant correlation with age, an effect that was most pronounced in older (>50 years of age) participants. This is the first validated longevity gene variant identified to date showing an association with negligible loss of telomere length with age in humans in a cross-sectional study. Reduced telomere attrition may be a key mechanism for the longevity-promoting effect of the FOXO3 genotype studied.